(untitled) (International Journal of Engineering and Computer Science, 2015)
The Multiple Travelling Salesman Problem (MTSP) is a generalization of the well-known TSP, where more than one salesman is allowed to be used in the solution. The characteristics of the MTSP seem more appropriate for real life applications. In this paper we study a problem called P-TSP Seasonal Constrained Model. Let there are number of cities ‘n’, the number of salesmen P, the third dimension is season S. Let M be common cities, which is subset of n for the salesman. Each salesman has to start their tour from head quarters that is city 1in first season only and at the end of the season 1 all the salesmen have to meet at a common city which is in ‘M’ . Again they starts their tour from common city in next season and visit some more cities and at the end of season 2 each of them have to meet at another common city which is in ‘M’ like this they travel upto (r-1)th season . Finally in rth season all the salesmen have to reach the head quarter city. All the salesman have to visit ‘n0’ cities other than the cities of ‘M’ that is n0< n-m. The objective is to complete p- tours in ‘r’ seasons with minimum total cost/distance.